Exploring the impact of a parenting information kit on experience of motherhood and maternal emotional wellbeing: a cluster randomised controlled trial. (September 2022) - Hay, Ms Sarah; Shafiei, Touran; McLachlan, Helen L; Newton, Michelle; Nicholson, Jan M; Grimes, Heather; McLardie-Hore, Ms Fiona; Forster, Della
Abstract : Background: There are considerable gaps in education for new families, particularly for the most vulnerable. A parenting education resource (the 'Kit'), developed by a tertiary hospital in Melbourne, Australia, aimed to provide evidence-based pregnancy and parenting information to prospective parents, from conception until one year after birth. The kit included; an educational book, an app and a children's story book. Aims: The trial aimed to evaluate the impact of the 'Kit' on women's experience of motherhood. Secondary aims were to evaluate the impact of the kit on maternal emotional wellbeing and parenting confidence. Methods: We undertook a two-arm cluster randomised controlled trial of first-time mothers, ≤30 weeks gestation, recruited at their pregnancy booking appointment. The intervention group received the Kit with content to be actively delivered by health professionals. The non-intervention group received standard hospital-based resources. Data were collected by telephone interview at six months assessing Experience of Motherhood Questionnaire (EMQ), and maternal emotional wellbeing using the Edinburgh Postnatal Depression Scale (EPDS) and Kessler 6 (K6). Findings: Of the 1034 women recruited, 599 women completed the follow-up interview; 301 and 298 in intervention and non-intervention arms respectively. Overall, there was no significant difference by trial arm for the EMQ ≤40 (n=415, 78.4% vs 75.6%, AOR 0.85 CI 0.53-1.36), EPDS ≥13 (n=351, 3.2% vs 3.1%, AOR 0.93 95% CI 0.27-3.19) and K6 ≥8 (n=352, 7.0% vs 9.0%, AOR 0.76, 95% CI 0.35-1.67) at six months after birth. Most women stated that their midwife or doctor never used the book (70%) or app (93%). Discussion and Conclusion: There was no significant difference between trial arms. This may be due to the dilution and/or delivery of the intervention. Further research in this area should ensure high level engagement with staff delivering new interventions further informing the provision of pregnancy and early parenting information.